ByzRev 06.2024.036: John Osborne, Rome in the Ninth Century.: A History in Art. Cambridge: Cambridge University Press 2023. - Labatt, Annie (The Byzantine Review, 2024)
John Osborne, Rome in the Ninth Century. A History in Art. Cambridge: Cambridge University Press 2023. xi+348 pp., 53 figs. – ISBN 978-1-009-41537-8